Tracking oseltamivir-resistance in New Zealand influenza viruses during a medicine reclassification in 2007, a resistant-virus importation in 2008 and the 2009 pandemic - Q Sue Huang; Jing Wang; Wendy Gunn; Molly Ziki; Mackenzie Nicol; Judy Bocacao; Jacqui C Ralston; Danielle J de Joux; Matthew Peacey; Richard J Hall (World Health Organization Regional Office for the Western Pacific, 2012)
Introduction: Oseltamivir (Tamiflu®) is an important pharmaceutical intervention against the influenza virus. The importance of surveillance for resistance to oseltamivir has been highlighted by two global events: the emergence of an oseltamivir-resistant seasonal influenza A(H1N1) virus in 2008, and emergence of the influenza A(H1N1)pdm09 virus in 2009. Oseltamivir is a prescription medicine in New Zealand, but more timely access has been provided since 2007 by allowing pharmacies to directly dispense oseltamivir to patients with influenza-like illness.Objective: To determine the frequency of oseltamivir-resistance in the context of a medicine reclassification in 2007, the importation of an oseltamivir-resistant seasonal influenza virus in 2008, and the emergence of a pandemic in 2009.Methods: A total of 1795 influenza viruses were tested for oseltamivir-resistance using a fluorometric neuraminidase inhibition assay. Viruses were collected as part of a sentinel influenza surveillance programme between the years 2006 and 2010.Results: All influenza B, influenza A(H3N2) and influenza A(H1N1)pdm09 viruses tested between 2006 and 2010 were shown to be sensitive to oseltamivir. Seasonal influenza A(H1N1) viruses from 2008 and 2009 were resistant to oseltamivir. Sequencing of the neuraminidase gene showed that the resistant viruses contained an H275Y mutation, and S247N was also identified in the neuraminidase gene of one seasonal influenza A(H1N1) virus that exhibited enhanced resistance.Discussion: No evidence was found to suggest that increased access to oseltamivir has promoted resistance. A probable importation event was documented for the global 2008 oseltamivir-resistant seasonal A(H1N1) virus nine months after it was first reported in Europe in January 2008.